Sociology of Hadith Learning at the Darul Abror Watumas Islamic Boarding School (Study of Text Authority, Gender and Student Agency) - Yenny Kusumaningrum; Muh. Hanif (Konsultan Jurnal Ilmiah Indonesia, 2026)
Islamic boarding schools (pesantren) are an important space in the study of the sociology of Islamic education the tradition of hadith scholarship with contemporary gender dynamics. This study highlights how hadith learning becomes a crucial arena for female students (santriwati) to understand their religious and social roles, and how the figure of the female teacher (nyai/ustazah) strengthens women's authority in Islamic education. The study aims to explain the process of hadith learning, the role of the female teacher (nyai/ustazah) as a scholarly authority for women, and the agency of female students in interpreting hadith texts to construct their identities and social roles. The research method uses a qualitative approach to pesantren gender studies through observation, interviews, and documentation. The results show: (1) female students study hadith on worship, morals, family, and women's social roles; (2) female teachers (ustazah) act as scholarly authority figures for women; and (3) female students interpret hadith to understand their roles in education, family, and society. This research contributes to the study of hadith learning, the development of Islamic education, and the quality of women's Islamic boarding schools (pesantren).